Piagam Madinah sebagai Model Multikulturalisme Islam untuk Pengelolaan Keragaman di Indonesia - Faqia, Dani Mahdi; Karomi, Kholid; Sansayto, Tistigar; Nasif, Hifni; Yahya, Yuangga Kurnia (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2025)
This research is motivated by the complexity of Indonesia's social, cultural, and religious diversity, which often triggers incidents of intolerance. The aim of this study is to examine how the concept of multiculturalism implemented by Prophet Muhammad SAW in the Charter of Medina can serve as a model for managing diversity in Indonesia. This research employs a qualitative method with a library research approach. Data were collected from primary sources such as the text of the Charter of Medina and classical historical texts, as well as secondary sources including journals, books, and previous relevant studies. Data collection was conducted through documentation, and the analysis used content analysis techniques with descriptive and comparative approaches. The findings indicate that the Charter of Medina embodies multicultural principles that ensure equal rights, freedom of religion, and inter-community cooperation, including the protection of minority groups. The charter successfully unified the plural and conflict-prone society of Medina into an organized and peaceful community. The conclusion of this study is that the values within the Charter of Medina can serve as an inspirational model for managing diversity in Indonesia, particularly in strengthening tolerance, social harmony, and national unity. This study recommends further research to explore the implementation of these values in public policy and multicultural education in Indonesia.